Productivity performance of Kangayam cattle - NATARAJAN, AKILA; K, SENTHILVEL; K, VELUSAMY (The Indian Journal of Animal Sciences, 2012)
Kangayam cattle, is a dual purpose breed and used more for carting. The present study was undertaken to find out the production performance of Kangayam cattle in Karur District. From the district 60 Kangayam cattle owners were identified randomly. The milk yield of the selected animals was recorded twice daily. As the calf and the farmer shared the milk the milk yield data were considered as daily partial milk yield. In addition milk samples were collected both morning and evening for estimation of milk constituents. The study reflected that the maximum lactation yield recorded among 60 animals was 1,455 litres and minimum of 342 litres. The milk yield in the first month (3.81litres) got increased to 4.11 litres in the second month. Almost the production in first 6 months is around 3.9 litres. The average fat per cent in Kangayam milk was found 3.9±0.07 and the SNF was 8.2±0.02 in the entire lactation period.